Minimization of Uranium Process Blank During Chemical Treatments of a Swipe Sample - Lee, Sunyoung; Ha, Young-Geun; Lee, Seon-A; Park, Jong-Ho; Song, Kyuseok (Asian Journal of Chemistry, 2013)
A uranium background derived from the chemical treatment of a swipe sample was determined using multi-collector inductively coupled plasma mass spectrometry. Prior to the mass spectrometric analysis, sequential acid digestion and chemical separation can be utilized to avoid polyatomic ion interference. This chemical process may increase the amount of uranium in the process blank, which has an effect on an accurate isotopic measurement of uranium in the sample. As a result of a uranium background analysis, a significant portion of uranium in process blank was provided from a plutonium elute solution used for chemical separation. Careful treatments for cleaning bottles and using pure reagents reduce the amount of uranium in the process blank. Additionally, the uranium background can be controlled by checking the amount of uranium in each process. An isotope dilution mass spectrometry technique was utilized to determine ultra-trace uranium (pico-gram level) in the process blank. An isotopic analysis was also performed by varying the concentration of HNO3 (DI, 3 % and 5 % of HNO3) used to dissolve the sample for mass spectrometric measurements.